Job Stress and Organizational Resources as Predictors of Teachers Psychological Well-Being: A JD–R-Based Study in Semarang - Yuliani Setyaningsih; Ida Wahyuni; Ekawati Ekawati; Dina Lusiana Setyowati; Risa Septi Astutik (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Teacher Psychological Well-Being (PWB) is increasingly recognized as vital to educational effectiveness, yet empirical studies in low and middle-income countries remain limited. This study investigates the predictors of PWB among senior high school teachers in Semarang, Indonesia, using the Job Demands–Resources (JD–R) model. A cross-sectional analytic design was employed, involving all 290 teachers from six public schools. Data were collected through validated questionnaires measuring job stress, organizational climate, career development, working conditions, and well-being, alongside demographic variables. Descriptive statistics, Spearman correlations, and multivariate logistic regression were used to analyze the data. Results showed that over half of the participants experienced high job stress, and 46.2% reported low psychological well-being. Regression analysis identified job stress as the strongest negative predictor (OR = 6.521), while favorable organizational climate (OR = 2.849), career development opportunities (OR = 2.492), and supportive working conditions (OR = 2.422) were significant positive predictors. Gender and education also influenced well-being, with female teachers and those with lower levels of educational reporting poorer outcomes. The model explained 42.1% of the variance in well-being and demonstrated high classification accuracy (78.6%). These findings emphasize the importance of addressing systemic and organizational factors rather than focusing solely on individual coping in promoting teacher well-being. The study validates the JD–R framework in an Indonesian context and offers evidence-based insights for educational reform. These results highlight actionable levers for schools and policymakers, including workload rationalization, strengthening supportive climates, and institutionalizing equitable professional development to improve teacher well-being. Longitudinal research is recommended to assess the long-term impact of targeted interventions.